Effect of black sesame (Sesamum indicum) and flaxseed flour (Linum usitatissimum) on bread quality using surface response methodology. - Audino Zambelli, Rafael; Freitas Pinto, Luan Ícaro; dos Santos Junior, Edilberto Cordeiro; Vieira de Lima, Ana Carolina; Lima Goiana, Mayara; de Mendonça, Luciana Gama; Guerra Rodrigues, Bárbara (Journal of Engineering & Processing Management, 2018)
The study aimed to evaluate the effect of black sesame and flaxseed flour addition in different proportions on bread quality. The bread formulations were developed through the Rotational Central Composite Design (RCCD). The independent variables were: black sesame and flaxseed flour which incorporated in amounts from 25.85% to 54.15%. The effect of the ingredients on bread quality was evaluated through physical parameters (specific volume, expansion index and volume produced). Statistical analysis was performed using response surface methodology and the two formulations with better technical performance were submitted to proximate composition (moisture, protein, fat, ash, carbohydrates and calcium), crumb structure, scanning electron microscopy (SEM) and sensorial analysis. It has been found that black sesame promotes greater reductions in the mass expansion capacity than flax meal. There was an improvement in the nutritional value of the loaves by increasing the protein content, ashes, fat and calcium, in addition to the reduction of carbohydrates. The breads developed had good acceptability in all evaluated attributes. In this way, the inclusion of black sesame and flaxseed flour as ingredients in bread formulations promotes products with technological and sensorial quality.